Pendampingan Masyarakat dalam Pengolahan Sampah Rumah Tangga Dengan Penerapan Teknologi Tepat Guna di Desa Sambijajar Kecamatan Sumbergempol Kabupaten Tulungagung - Darjati Darjati; Rusmiati Rusmiati; Umi Rahayu; A.T. Diana Nerawati (LPPM UNINUS, 2022)
The problem of household/kitchen waste cannot be separated from people's lives, both in cities and in densely populated villages. If it is not handled properly from waste sources it can cause health and environmental problems. To reduce this, it can be done by processing it into compost, one of which is the Takakura method. Sambijajar village, Sumbergempol sub-district, Tulungagung regency, the amount of waste generation/day is around 568 kg with the problem of littering, burning in the front or back of the house, narrow land so that it is not properly organized, there is buildup and smell and causes air pollution, smoke from burning trash. So processing waste into compost (takakura method) is expected to be able to solve this problem independently on a household scale. So this method is very appropriate as an appropriate technology in solving the problem of landfills in the community, through direct community empowerment. The purpose of this community service activity with the theme of developing Mitra Village is to make people care about the environment independent by increasing their knowledge, and skills and applying the Takakura method of waste management. The form of the activity is training in processing waste using the Takakura method of Appropriate Technology. The methods used are counseling and training. The results obtained from this activity are that the community can improve community knowledge and skills in processing waste into compost using the takakura method. This activity was attended by more than 50 local people as fruit seed farmers and MSMEs as waste producers.